New empirical methods for predicting flexural capacity and stiffness of CFST beam. (January 2020) - Al Zand, Ahmed W.; Badaruzzaman, Wan Hamidon W.; Tawfeeq, Wadhah M.
Abstract: This paper presents new empirical methods to theoretically predict bending moment capacity ( M u ) and flexural stiffness values at the initial and serviceability levels ( K i and K s ) of concrete-filled steel tube (CFST) composite beams. A wide range of results for M u, K i, and K s covering various parameters of CFST beams are required to develop these empirical methods. Therefore, 144 numerical CFST models were developed in this study using finite element software. The adequacy of the newly developed empirical methods was validated with the results obtained from previously reported experimental and numerical studies conducted by other researchers. For example, using the new methods, mean values of 0.967 and 0.996 were achieved from the ratios of predicting M u values to the previously reported values of the rectangular and circular CFST beams, respectively. The mean values were 1.074 and 1.050 from the predicted K i, and K s values, respectively. Furthermore, the results of these new methods were compared with the results obtained by the most commonly used standards and methods in this field, namely, EC4, AISC, AIJ, BS5400, and others. Highlights: Developed new empirical methods to predict the moment capacity of CFST beams. Developed new empirical method to predict the flexural stiffness of CFST beams at the initial and serviceable levels. The new methods well validated with the existing results obtained by other researchers. The new methods well compared to the existing code standards and methods.